Diurnal Fluctuations in Rectal Temperature of Black Harco Pullets Administered with Vitamins A and C During the Hot-Dry Season - Sinkalu, V.O.; Ayo, J.O. (International Journal of Poultry Science, 2008)
Experiments were performed with the aim of determining the effect of co-administration of vitamins A and C on rectal temperature (RT) fluctuations in pullets during the hot-dry season. RTs of 29 experimental and 20 control Black Harco pullets were measured hourly for three days, three days apart, from 06:00 to 19:00 h with a standard digital clinical thermometer. The experimental pullets were administered individually with vitamins A and C orally at a daily dose of 1,200IU/kg and 50mg/kg, respectively. The control pullets were given only water, without the addition of vitamins A and C. The lowest hourly RT of 40.96±0.03oC was obtained in experimental pullets at 06:00 h, while the highest value of 41.28±0.02oC was recorded at 16:00 h (P < 0.001). In control pullets, the RT rose significantly from 40.97±0.05oC at 06:00 h to the maximum value of 41.61±0.03oC at 15:00 h (P < 0.001). There was a positive and very highly significant (P < 0.001) correlation between hours of the day and RT values obtained both in experimental (r = 0.834) and control (r = 0.884) pullets. The overall RT of pullets administered with vitamins A and C was significantly (P < 0.05) lower than that of control pullets (41.16±0.02oC and 41.39±0.05oC, respectively). The dry-bulb temperature was significantly (P < 0.001) and positively correlated with RT in both experimental (r = 0.936) and control (r = 0.969) pullets. The pullets administered with vitamins A and C had consistently lower RT values than those of control pullets, especially during the hot hours of the day, from 13:00-18:00 h, with mean values fluctuating between 41.19±0.02oC and 41.28±0.02oC. The RT of both experimental and control pullets showed distinct diurnal fluctuations. It is concluded that vitamins A and C, by reducing the RT values, ameliorated the thermally stressful effect of the hot-dry season and this mechanism may be partly involved in the enhancement of poultry productivity and health during the season by antioxidant vitamins.